Developmental delays in emotion regulation strategies in preschoolers with autism. Issue 11 (11th July 2017) - Nuske, Heather J.; Hedley, Darren; Woollacott, Alexandra; Thomson, Phoebe; Macari, Suzanne; Dissanayake, Cheryl
Abstract : Children with autism spectrum disorder (ASD) commonly present with difficulty regulating negative emotions, which has been found to impact their behavioral and mental health. Little research has documented the strategies that children with ASD use to regulate their emotion to understand whether they use qualitatively different strategies to children without ASD, whether these are developmentally delayed, or both. Forty‐four children with ASD and 29 typically‐developing children (2–4 years) were given tasks designed to mimic everyday life experiences requiring children to manage low‐level stress (e.g., waiting for a snack) and children's emotion regulation strategies were coded. Parents reported on their child's mental health, wellbeing, and self‐development. The results suggest differences in using emotion regulation strategies in children with ASD, reflecting a delay, rather than a deviance when compared to those used by children without ASD. Only children with ASD relied on their family members for physical and communicative soothing; the typically developing children relied on people outside of their family for help regulating their emotion. More frequent approach/less frequent avoidance was related to a higher self‐evaluation in both groups, but was only additionally related to higher self‐recognition and autonomy in the ASD group. These findings help to identify important emotion regulation intervention targets for this population, including supporting communication with people outside of the family and independence. Autism Res 2017, 10: 1808–1822 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Results suggest that children with autism had more difficulty using communication strategies to manage stress only with people outside the family; they used these strategies with family members as often as children without autism. For all children, more task approach/less avoidance was related to children's higher self‐evaluation. These findings suggest targeting communication with people outside of the family and personality development as appropriate intervention goals.